Memanusiakan Manusia: Konseling Pendidikan Kristiani dalam Mengatasi Sikap Apatis Remaja - Manalu, Johanes; Arisman; Sitorus, Johnson; Ndraha, Amoli; Sukatman, Kristian (Sekolah Tinggi Teologi Torsina Surakarta, 2024)
The rapid development of technology has become a means for human needs to carry out various activities, and it has even become a place to make money. The use of gadgets, a technology that is so sophisticated and almost owned by every group, makes humans dependent on gadgets. This paper studies how the use of gadgets causes the loss of social interest in adolescents and how its influence causes apathy in adolescents. This research focuses on the use of gadgets by adolescents and their influence on the attitudes and behavior of adolescents in their environment. The aim is to look at the development of adolescents through the progress of today's times and how to react to it so that they remain on the right track and do not deviate from the teachings of the Word of God. The author uses a qualitative method with a literature study approach to review and analyze topics from various sources, such as journals, books, and the Internet, that are relevant to the discussion of writing. The influence of gawais erodes the attitude of respect, and respect affects social interest and becomes apathetic, so a good mentor who can monitor teenagers' activities and self-control from the teenagers themselves so that the wrong dependence on the use of gawais does not carry them away. Abstrak Perkembangan teknologi yang begitu pesat menjadi sarana kebutuhan manusia untuk melakukan berbagai aktifitas, bahkan telah menjadi wadah untuk mencari uang. Penggunaan gawai yang adalah bentuk teknologi canggih yang hampir dimiliki setiap kalangan, membuat manusia bergantung pada gawai. Dalam penulisan ini mengkaji bagaimana penggunaan gawai mempengaruhi peranan remaja sebagai manusia yang adalah makhluk sosial, terhadap lingkungan sekitarnya. Penelitian ini berfokus pada penggunaan gawai oleh remaja upaya mengatasi sikap apatis. Tujuannya untuk melihat perkembangan remaja melalui kemajuan zaman saat ini dan bagaimana cara menyikapinya supaya tetap dijalur yang baik dan benar, yang tidak menyimpang dari ajaran Firman Tuhan. Penulis menggunakan metode kualitatif dengan pendekatan studi pustaka dan literatur untuk mengkaji dan menganalisis topik dari berbagai sumber seperti jurnal, buku, internet yang relevan dengan pembahasan penulisan. Pengaruh gawai mengikis sikap hormat dan respek yang memengaruhi minat sosial dan menjadi apatis, sehingga dibutuhkan mentor yang baik yang dapat memantau aktivitas remaja serta pengendalian diri dari remaja itu sendiri supaya tidak terhanyut pada ketergantungan yang salah pada penggunaan gawai.